Inflammatory angiomyolipoma of the liver: a rare hepatic tumor - Liu Yang; Wang Jian; Lin Xu-Yong; Xu Hong-Tao; Qiu Xue-shan; Wang En-Hua (BMC, 2012)
Abstract Angiomyolipoma (AML) is a rare mesenchymal neoplasm of the tumor, composed of a varying heterogeneous mixture of three tissue components: blood vessels, smooth muscle and adipose cells. Hepatic AML may demonstrate a marked histological diversity. We herein present one case of hepatic AML exhibiting prominent inflammatory cells in the background, which happened in a 61-year-old Chinese female patient, without signs of tuberous sclerosis. Histologically, the striking feature was the infiltration of numerous inflammatory cells in the background, including small lymphocytes, plasma cells, and eosnophils. The tumor cells were spindled and histiocytoid in shape, with slightly eosinophilic cytoplasm, and arranged along the vessels or scattered among the inflammatory background. Sinusoid structure was obviously seen in the tumor. Mature adipocytes and thick-walled blood vessels were focally observed at the boundaries between the tumor and surrounding liver tissues. The tumor cells were positive immunostaining for HMB-45, Melan-A, and smooth muscle actin. The inflammatory AML should be distinguished from other tumors with inflammatory background such as inflammatory myofibroblastic tumor and follicular dendritic cell tumor and deserves wider recognition for its occurrence as a primary hepatic tumor. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1828633072762370